Perceived Normalization of Drug Trafficking and Adolescent Substance Use on the US–Mexico Border. (July 2022) - Valdez, Elizabeth Salerno; Obeng-Kusi, Mavis; Brady, Benjamin; Huff-Macpherson, Allison; Bell, Melanie; Derose, Kathryn
Adolescents residing on the US–Mexico border are at disproportionate risk for substance misuse due to environmental risk factors, including high unemployment, high concentration of liquor licenses, drug-trade–related violence, border militarization, and inadequate access to prevention, treatment, and support services for substance misuse. We used multivariable logistic regression to examine the association between high perceived normalization of drug trafficking and cross-border purchase, and past 30-day substance use (tobacco, alcohol, and marijuana) in a sample of 445 primarily Mexican American adolescents living on the US–Mexico border. Adolescents with higher perceived normalization of drug trafficking scores were more likely to have crossed the border to purchase (OR = 1.17, 95% CI 1.07, 1.28) and use substances (OR = 1.08, 95% CI 1.00, 1.17). The economic and normative environment of border communities must be considered in the formation of interventions targeted at substance use risk prevention and mitigation, and involve binational support from organizations, policy makers, and community members.